An introduction to combustion concepts and applications - Turns, Stephen R. (McGraw-Hill series in mechanical engineering, 1996)
Targeted at senior and first year graduate level courses in combustion, this text covers more material than can be covered in a single semester course, but at a level that is easily comprehended by undergraduate students. There is a tremendous need for undergraduate students interested in the thermal sciences to have a basic knowledge of combustion science and its applications. This text is the first to present the essential theory and background material that is helpful for understanding the more complex literature on combustion, in a format that is teaching rather than reference oriented. The theory is reinforced by examples, review questions and problems within each chapter.